Front page - AIC - ICMR 2017 - AIC Committe AIC Committe (Proceedings of AICS - Social Sciences, 2017)
It is an honour to welcome you to the 7th AIC-ICMR 2017 International Conference. The conference will be held on October 18-20, 2017, in Banda Aceh, Aceh Province, Indonesia. This conference is hosted by Syiah Kuala University (recognizably abbreviated as UNSYIAH), the largest and the oldest national university in Aceh. The annual event on 2017 is co. organized by Universiti Sains Malaysia (USM), Universitas Islam Sumatera Utara (UISU), Universitas Hasanuddin (Unhas), and the Cooperation Agency of Public Universities in the Western Region of Indonesia (BKS PTN Barat).The annual event on 2017 is jointly conference between the 7th Annual International Conference (AIC) Syiah Kuala University and The 6th International Conference on Multidisciplinary Research (ICMR). The AIC is an annual international conference carried out regularly by Syiah Kuala University since 2011. The ICMR is an annual event which has been jointly organized by UNSYIAH, USM, UISU and UNHAS since 2012The 7th AIC-ICMR 2017 are divided into three multidisciplinary conferences: the 7th AIC-ICMR on Sciences and Engineering, the 7th AIC-ICMR on Health and Life Sciences, and the 7th AIC-ICMR on Social Sciences. This year, the 7th AIC-ICMR will be held in conjunction with the International Conference on Electrical Engineering and Informatics (ICELTICs) 2017.The AIC-ICMR 2017 will provide an excellent forum for sharing knowledge and research findings among academicians, professionals, and governments. Topics of interests cover all theoretical and practical aspects of Sciences and Engineering, Health and Life Sciences, and Social Sciences. The primary goal AIC-ICMR 2017 is organized to promote multidisciplinary understanding of the latest research and innovations through discussion, exchange, and sharing among researcher, practitioners, academicians and students.